The little big number : how GDP came to rule the world and what to do about it - Philipsen, Dirk, 1959- (Princeton University Press, 2015)
"In one lifetime, GDP, or Gross Domestic Product, has ballooned from a narrow economic tool into a global article of faith. It is our universal yardstick of progress. As The Little Big Number demonstrates, this spells trouble. While economies and cultures measure their performance by it, GDP ignores central facts such as quality, costs, or purpose. It only measures output: more cars, more accidents; more lawyers, more trials; more extraction, more pollution--all count as success. Sustainability and quality of life are overlooked. Losses don't count. GDP promotes a form of stupid growth and ignores real development. How and why did we get to this point? Dirk Philipsen uncovers a submerged history dating back to the 1600s, climaxing with the Great Depression and World War II, when the first version of GDP arrived at the forefront of politics. Transcending ideologies and national differences, GDP was subsequently transformed from a narrow metric to the purpose of economic activity. Today, increasing GDP is the highest goal of politics. In accessible and compelling prose, Philipsen shows how it affects all of us. But the world can no longer afford GDP rule. A finite planet cannot sustain blind and indefinite expansion. If we consider future generations equal to our own, replacing the GDP regime is the ethical imperative of our times. More is not better. As Philipsen demonstrates, the history of GDP reveals unique opportunities to fashion smarter goals and measures. The Little Big Number explores a possible roadmap for a future that advances quality of life rather than indiscriminate growth."--